Whitehead's metaphysics of creativity - Rapp, Friedrich; Wiehl, Reiner (State University of New York Press, 1990)
Whitehead and the dichotomy of rationalism and empiricism / Ivor Leclerc -- Whitehead and Berkeley : on the true nature of sense perception / Ernest Wolf-Gazo -- Whitehead's interpretation of Locke in process and reality / Rainer Specht -- Creativity and the passage of nature / Dorothy Emmet -- Whitehead's concept of creativity and modern science / Friedrich Rapp -- Whitehead's cosmology as revisable metaphysics / Hans Poser -- What one thinks : singular propositions and the content of judgements / Wolfgang Künne -- Whitehead's cosmology of feeling between ontology and anthropology / Reiner Wiehl -- Which experiences teach us to understand the world? : observations on the paradigm of Whitehead's cosmology / Robert Spaemann -- Atom, duration, form : difficulties with process philosophy / Wolfhart Pannenberg -- Creativity as universal activity / Jan Van der Veken -- Creativity : a new transcendental? / Reto Luzius Fetz.